Uterine Leiomyoma in a Guyanese Squirrel Monkey (Saimiri sciureus sciureus) - Long, C Tyler (American Association for Laboratory Animal Science, 2010)
An adult female squirrel monkey (Saimiri sciureus) presented with a 3.0 × 2.5 cm firm mass palpable within the caudal abdomen. Differentiation of the organs or structures involved with the mass could not be achieved with radiography or ultrasonography. Exploratory laparotomy revealed a mass within the lumen of the uterus; the mass was removed by partial hysterectomy. On gross examination, the mass was a focally extensive, unencapsulated, firm, solitary tumor. Histologic examination revealed that the mass was composed of interlacing bundles of smooth muscle cells with little fibrous stroma. The cells were elongated with poorly delineated borders and cigar-shaped nuclei, each containing a single, small nucleolus. Fewer than 1 mitosis per 20 high-power (magnification, × 400) fields were present. These gross and histologic findings supported a diagnosis of uterine leiomyoma. Although leiomyomas are the most common tumor of the reproductive tract in nonhuman primates, to our knowledge the current lesion is the first uterine leiomyoma reported to occur in a squirrel monkey.